Statistical Fluid Dynamics - Ammar, Amine; Chinesta, Francisco; Valette, Rudy (MDPI - Multidisciplinary Digital Publishing Institute, 2022)
Modeling micrometric and nanometric suspensions remains a major issue. They help to model the mechanical, thermal, and electrical properties, among others, of the suspensions, and then of the resulting product, in a controlled way, when considered in material formation. In some cases, they can help to improve the energy transport performance. The optimal use of these products is based on an accurate prediction of the flow-induced properties of the suspensions and, consequently, of the resulting products and parts. The final properties of the resulting micro-structured fluid or solid are radically different from the simple mixing rule. In this book, we found numerous works addressing the description of these specific fluid behaviors.